2013
DOI: 10.1016/j.str.2012.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Phosphorylated SF1 Bound to U2AF65 in an Essential Splicing Factor Complex

Abstract: SUMMARY The essential splicing factors U2AF65 and SF1 cooperatively bind consensus sequences at the 3′ end of introns. Phosphorylation of SF1 on a highly conserved ‘SPSP’ motif enhances its interaction with U2AF65 and the pre-mRNA. Here we reveal that phosphorylation-induces essential conformational changes in SF1 and in the SF1/U2AF65/3′ splice site complex. Crystal structures of the phosphorylated (P)SF1 domain bound to the C-terminal domain of U2AF65 at 2.29 Å resolution, and of the unphosphorylated SF1 dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 54 publications
6
80
3
Order By: Relevance
“…As discussed below, a structure of the U2AF 65 UHM bound to the N-terminal domain of SF1 further revealed that regions beyond the minimal ULM stabilize this masked UHM conformation ( Fig. 3B; Wang et al 2013;Zhang et al 2013). It is possible that analogous, ligand-mediated reinforcements of the α-helical block on the UHM "RNA binding surface" will emerge as more UHM-containing structures are determined bound to intact, ULM-containing proteins.…”
Section: Do Uhms Bind Rna?mentioning
confidence: 93%
See 4 more Smart Citations
“…As discussed below, a structure of the U2AF 65 UHM bound to the N-terminal domain of SF1 further revealed that regions beyond the minimal ULM stabilize this masked UHM conformation ( Fig. 3B; Wang et al 2013;Zhang et al 2013). It is possible that analogous, ligand-mediated reinforcements of the α-helical block on the UHM "RNA binding surface" will emerge as more UHM-containing structures are determined bound to intact, ULM-containing proteins.…”
Section: Do Uhms Bind Rna?mentioning
confidence: 93%
“…Phosphorylation of this site by cGMP-dependent protein kinase-I reduces SF1 association with U2AF 65 and thereby inhibits spliceosome assembly. Structurally, the phosphorylated SF1 S20 would disrupt a hydrogen bond and electrostatically repel a conserved aspartate residue (D401) in the acidic α-helix of the U2AF 65 UHM (Wang et al 2013). Two of the SF3b155 ULMs display serine residues at analogous positions as SF1 S20, including SF3b155 S216 and S336 in ULM2 and ULM5; phosphorylation of SF3b155 S216 has been confirmed in an acute myeloid leukemia cell line by mass spectrometry (Weber et al 2012).…”
Section: Ulm Phosphorylation Regulates Partnerships With Uhmsmentioning
confidence: 94%
See 3 more Smart Citations